COMPARATIVE-TYPOLOGICAL STUDY OF CONDITIONALS IN LITERARY TEXTS (English and Uzbek materials) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Conditional sentences are the complex sentences, which consist of two sub-clauses namely “if-clause” and “main clause”. Conditionals are considered as a problematic sphere of English language for both learners and scholars. The main obstacles in “If” sentences are their form, sequences of tenses and the connected meaning of the two clauses. Besides that majority L1 speakers are confused during the translation and conception because of not having abundant proficiency not only in target language but also in their own native language.